A New Approach to Measure Gas Holdup in Industrial Flotation Machines. Part Iii: Industrial Prototype Design and Assessment - Maldonado-Saavedra, M (Elsevier Ltd, 2022)
An industrial gas holdup sensor was designed, constructed, and its performance assessed on a 250 m3 self-aerated Wemco cell at Los Pelambres concentrator. The submersible sensor comprised a ceramic-liner IP68 magnetic flowmeter assembled to a stainless steel gas exclusion cell, which resembles an inverted truncated cone. The gas exclusion cell was designed to avoid low-velocity sections where particles could settle. When the sensor device is vertically immersed in an aerated pulp a continuous downward flow of pulp without bubbles is induced through it. A remotely installed processing unit converts the flow velocity signal, provided by the magnetic meter, into a gas holdup signal, by applying Bernoullís equation to the induced flow. The ideal velocity in the Bernoullís equation is obtained by multiplying the measured velocity and the discharge coefficient. The discharge coefficient was found to be fairly constant over a wide range of Reynolds numbers. Gas holdup measurements were compared against those obtained by sampling a fixed volume of aerated pulp using the JK Tech Air Holdup Probe. These tests were conducted on different days over nine months to allow for the pulp properties to change. Gas holdup changes in the flotation machine were achieved by restricting the air intake to the cell by placing a stainless steel cap on top of the air suction pipe. Short and long-term testing demonstrated the sensoŕs capability to provide reliable and accurate continuous-time gas holdup measurements for industrial flotation machines. © 2022